2014
DOI: 10.1371/journal.pone.0087121
|View full text |Cite
|
Sign up to set email alerts
|

Workload Influence on Fatigue Related Psychological and Physiological Performance Changes of Aviators

Abstract: ObjectiveWe evaluated a variety of non-invasive physiological technologies and a series of test approaches for examination of aviator performances under conditions of mental workload in order to provide a standard real-time test for physiological and psychological pilot fatigue assessments.MethodsTwenty-one male aviators were selected for a simulated flight in a hypobaric cabin with artificial altitude conditions of 2400 meter above sea level. The simulated flight lasted for 1.5 h, and was repeated for two tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…Measurements used for recognizing fatigue among pilots were discussed in different articles. For example, Ma et al (2014) evaluated a series of test approaches (subjective and objective reports of fatigue) for pilot performance examination under mental workload conditions and found out that critical flicker fusion frequency (CFF) test was the easiest way to detect mental workload. Taneja (2007) constructed questionnaire for measuring fatigue (about sleep, circadian rhythms, shift work, understanding of fatigue and countermeasures).…”
Section: Source: Authorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Measurements used for recognizing fatigue among pilots were discussed in different articles. For example, Ma et al (2014) evaluated a series of test approaches (subjective and objective reports of fatigue) for pilot performance examination under mental workload conditions and found out that critical flicker fusion frequency (CFF) test was the easiest way to detect mental workload. Taneja (2007) constructed questionnaire for measuring fatigue (about sleep, circadian rhythms, shift work, understanding of fatigue and countermeasures).…”
Section: Source: Authorsmentioning
confidence: 99%
“…Our aim was to identify the tendencies in the literature about measuring fatigue among pilots. Ma et al (2014) argued that CFF may become a novel method to evaluate mental workload of pilots, which influences their mental conditions and is the easiest way to evaluate mental workload to fatigue. Petrie and Dawson (1997), using Self-Constructed Fatigue Questionnaire (symptoms, coping strategies of fatigue), suggested that symptoms of fatigue can be grouped into five categories: cognitive dysfunction, sleepiness, emotional disturbance, boredom and physical effects.…”
Section: Source: Authorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ma et al (2014) evaluated a variety of non-invasive physiological technologies and a series of test approaches for examination of aviator performances under conditions of mental workload in order to provide a standard real-time test for physiological and psychological pilot fatigue assessments. Ma et al (2014) evaluated a variety of non-invasive physiological technologies and a series of test approaches for examination of aviator performances under conditions of mental workload in order to provide a standard real-time test for physiological and psychological pilot fatigue assessments.…”
Section: Hypotheses and Structural Equation Modelmentioning
confidence: 99%